A novel gene-based therapy for galaucoma:from discovery to preclinical development - O'CALLAGHAN, JEFFREY (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2018)
Introduction: Glaucoma is a multifactorial condition that will often result in complete bilateral blindness if untreated. Elevated intraocular pressure (IOP) is both a major risk factor and indicator of disease. IOP is maintained by the balance between production of aqueous humour (AH) by the ciliary processes and hydrodynamic resistance to its outflow through the conventional outflow pathway comprising the trabecular meshwork (TM) and Schlemm?s canal (SC). Since a significant proportion of glaucoma patients develop resistance to pressure-reducing topical formulations, there remains a significant unmet clinical need for medications acting upon the conventional pathway. Matrix metalloproteinases (MMPs) contribute to conventional aqueous outflow homeostasis through their capacity to remodel extracellular matrices, which has a direct impact on aqueous outflow resistance and IOP. In this regard, an AAV-mediated gene therapy targeting the conventional outflow pathway using an MMP secreted from the corneal endothelium into the anterior chamber, increasing AH outflow and reducing IOP has been developed in mice following intracameral inoculation. Methods: TEER and flux assays were performed on SC and TM monolayers to observe the effect of multiple cytokines on permeability. RT-PCR and western blot was used to identify levels of MMP expression in response to such cytokines. Healthy and glaucomatous AH were assayed by ELISA and FRET to quantify the concentration and activity of MMP-3. Recombinant MMP-3 was further assayed for its effect on monolayer permeability. An AAV-2/9 containing a CMV or tetracycline promoter-driven MMP-3 gene was intracamerally injected into wild type mice and into mice modelling glaucoma induced by dexamethasone or by expression of a dominant-acting human myocilin transgene. Immunohistochemistry was performed on anterior segment cryosections to assess MMP-3 expression in the anterior chamber and immunocytochemistry/western blot were performed to ascertain substrate cleavage. IOP and outflow facility readings were performed on injected murine eyes to ascertain the effect of virally delivered MMP-3 on AH flow dynamics. Transmission electron microscopy was used to observe the physical effect of treatment on the outflow pathway. Results: MMP-3 was identified as an attractive target for secretion into the anterior chamber. Decreased MMP-3 activity was observed in human glaucomatous AH compared to age-matched normotensive control AH. Treatment with glaucomatous AH resulted in significantly increased transendothelial resistance of SC endothelial and TM cell monolayers, and reduced monolayer permeability when compared to control AH or supplemented treatment with exogenous MMP-3. Intracameral inoculation of AAV-2/9 containing a CMV-driven MMP-3 gene (AAV-MMP-3) into wild type mice resulted in efficient transduction of corneal endothelium and an increase in aqueous concentration and activity of MMP-3. Most notably, AAV-mediated expression of MMP-3 increased outflow facility and decreased IOP. Controlled expression using an inducible promoter activated by topical administration of doxycycline achieved the same effect in both steroid-induced and genetically engineered murine models of glaucoma. Ultrastructural analysis of MMP-3 treated matrices revealed remodelling and degradation of core extracellular matrix components. These results indicate that periodic induction, via use of an eye drop, of AAV-mediated secretion of MMP-3 into AH could have therapeutic potential for those cases of glaucoma that are sub-optimally responsive to conventional pressure-reducing medications. Preliminary data on successful AAV-mediated transfection of corneal endothelia in non-human primates are also presented.
APPROVED
Keywords: MMP3; Matrix metaloproteinase; Gene therapy; Adeno associated virus; corneal endothelium; conventional outflow; IOP; Glaucoma; outflow facility